Teaching for the 21st Century: Indigenising the Law Curriculum at UWA - Ambelin Kwaymullina (Legal Education Review, 2020)
The Law School and the School of Indigenous Studies at the University of Western Australia (UWA) have embarked on a project to ‘Indigenise’ the UWA Juris Doctor (JD) degree. For the purposes of the project, ‘Indigenise’ is defined as the incorporation of Indigenous knowledges, cultures and experiences throughout the JD in a way that is consistent with our Principles of Indigenisation (see Part IV below).